The BFG - Dahl, Roald; Blake, Quentin (London : New York : Puffin, 1998)
Kidsnatched from her orphanage by a BFG (Big Friendly Giant), who spends his life blowing happy dreams to children, Sophie concocts with him a plan to save the world from nine other man-gobbling cannybull giants.
M
Originally published: London : J. Cape, c1982.
"Puffin books."
b
b
Keywords: Giants -- Fiction; Orphans -- Fiction